FEMPIRICAL STUDY OF COMMUNICATIVE COMPETENCE OF FUTURE TEACHERS - Теслюк, Валентина; Паскаленко, Ольга (SWorldJournal, 2021)
The article presents an empirical study of communicative competence of future teachers. Qualitative assessment of the development of communicative competence of future teachers was conducted by analyzing quantitative indicators obtained through a set of p